2018
DOI: 10.1080/00131857.2018.1454000
|View full text |Cite
|
Sign up to set email alerts
|

Postdigital science and education

Abstract: We are increasingly no longer in a world where digital technology and media is separate, virtual, 'other' to a 'natural' human and social life. This has inspired the emergence of a new concept-'the postdigital'-which is slowly but surely gaining traction in a wide range of disciplines including but not limited to the arts (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
205
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 503 publications
(257 citation statements)
references
References 37 publications
2
205
0
8
Order By: Relevance
“…This paradigm could represent a shift from traditional, teacher-centered, and lecturebased activities towards more student-centered activities including group activities, discussions, hands-on learning activities, and limited use of traditional lectures. This requires conceptual and philosophical rethinking of nature of teaching and learning, roles, and connections among teachers, learners, and teaching materials, in postdigital learning communities (Jandrić et al 2018).…”
Section: Vision For Future: Teaching and Learning After The Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…This paradigm could represent a shift from traditional, teacher-centered, and lecturebased activities towards more student-centered activities including group activities, discussions, hands-on learning activities, and limited use of traditional lectures. This requires conceptual and philosophical rethinking of nature of teaching and learning, roles, and connections among teachers, learners, and teaching materials, in postdigital learning communities (Jandrić et al 2018).…”
Section: Vision For Future: Teaching and Learning After The Pandemicmentioning
confidence: 99%
“…In our postdigital context, online and offline (teacher) education cannot be thought of without each other (Jandrić et al 2018). Therefore, we advocate development of a holistic teacher education system, regardless of used mode of delivery, which could support present and future teachers in becoming more resilient to crisis similar to the Covid-19 pandemic.…”
Section: Vision For Future: Teaching and Learning After The Pandemicmentioning
confidence: 99%
“…However, not only are the identities of authors revealed here, their Covid-19 narratives are shaped also by the decisions of their governments, their university, technologies they communicate through, and multiple media accounts of what others are experiencing, in virtual and physical spaces, simultaneously. Such is the 'postdigital condition' (Jandrić et al 2018), where a messy, hybrid intertwining of the physical, biological, economical, and historical meets the technological, cultural, and personal. This is illustrated through a different form of prejudice, than simply an aversion to online education.…”
Section: Open Reviewmentioning
confidence: 99%
“…Companies monetize global panic and endanger public safety by increasing prices of necessary products (World Health Organization 2020b). These trends indicate a reconfiguration in complex relationships between knowledge, public health, and bio-informational capitalism, which results from this newest postdigital scenario (Jandrić et al 2018).…”
Section: Solidarity: Nmentioning
confidence: 99%
“…In our complex, messy and unpredictable postdigital condition (Jandrić et al 2018), struggle against these disturbing trends develops curious reconfigurations between the digital and the physical sphere. The digital has indeed become 'the master narrative of our world' (Fuller and Jandrić 2019: 215); yet, the biological is more important than ever.…”
mentioning
confidence: 99%